2018
DOI: 10.1055/s-0038-1636838
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Surgical Trends in the Management of Symptomatic Meniscal Tears among United States Military Servicemembers from 2010 to 2015

Abstract: IV, cross-sectional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…32,33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. [34][35][36][37] Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al 39 performed meniscal allograft transplant (MAT) alone on 222 patients and found this treatment to be effective in managing patients with advanced cartilage disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. [34][35][36][37] Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al 39 performed meniscal allograft transplant (MAT) alone on 222 patients and found this treatment to be effective in managing patients with advanced cartilage disease.…”
Section: Discussionmentioning
confidence: 99%
“…32 , 33 Meniscal surgery, either through transplant or repair, has significantly increased over the past decade, even with cartilage restoration procedures. 34 , 35 , 36 , 37 Addressing the meniscus allows repaired cartilage to have the greatest likelihood of successful implantation and preservation of joint integrity. 38 Lee et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent publications have sought to characterize surgical trends in the management of meniscal tears, rates of reoperation following meniscal repair, and meniscal tears in the setting of failed ACL reconstruction 12,23,24 (►Table 1). There are almost 5,000 meniscal procedures per year in the military.…”
Section: Epidemiology Of Meniscus Tears In the Militarymentioning
confidence: 99%
“…Two-thirds of meniscal repairs occur on the medial meniscus. 23 The overall rate of meniscal repair is 47.6 per 100,000 person-years. 12 In the setting of meniscal repair, the most common concomitant procedure performed is ACL reconstruction-similar to published civilian data.…”
Section: Epidemiology Of Meniscus Tears In the Militarymentioning
confidence: 99%
See 1 more Smart Citation